Latin tardif, francais ancien : continuites et ruptures - Carlier, Anne; Guillot-Barbance, Celine (Berlin ; Boston : De Gruyter, 2018)
Even though a rich written tradition documents the evolution from Latin to French, the crucial transition from Late Latin to Old French in the oral language remains partially obscure. Thanks to a corpus-based approach and the collaboration of Latinists and French historians, this edited volume sheds a new light on this "missing link".
Includes bibliographical references and indexes.
In French and English.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Latin language -- History; French language -- History; Electronic books